1991
DOI: 10.1161/01.cir.83.1.268
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant ventricular arrhythmias in the late myocardial infarction period: mechanism by which a short-long-short cardiac sequence facilitates the induction of reentry.

Abstract: The electrophysiological mechanism by which a short-long-short stimulated cardiac sequence facilitates the induction of ventricular tachyarrhythmia was investigated in dogs 4 days after ligation of the left anterior descending coronary artery. In these dogs, reentry develops in the surviving electrophysiologically abnormal epicardial layer that overlies the infarct zone when premature stimulation results in a critically long arc of functional conduction block. The activation wavefront circulates around both en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
4

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 34 publications
2
25
1
4
Order By: Relevance
“…In this setting, reentry can occur as the result of shortening of activation wavelength below the physical length of a preformed reentry circuit. [35][36][37] Conduction slowing and action potential shortening both shorten activation wavelength. Given little or no change in APD, a fourfold increase in conduction time as observed with propafenone in this study decreases activation wavelength fourfold (Table 4) and possibly below the perimeter of the heart, a setting that allows for macroreentry around the circumference of the whole heart in this model.…”
Section: Conduction Slowing Promotes Monomorphic Vtmentioning
confidence: 99%
“…In this setting, reentry can occur as the result of shortening of activation wavelength below the physical length of a preformed reentry circuit. [35][36][37] Conduction slowing and action potential shortening both shorten activation wavelength. Given little or no change in APD, a fourfold increase in conduction time as observed with propafenone in this study decreases activation wavelength fourfold (Table 4) and possibly below the perimeter of the heart, a setting that allows for macroreentry around the circumference of the whole heart in this model.…”
Section: Conduction Slowing Promotes Monomorphic Vtmentioning
confidence: 99%
“…As described by Gelzer et al27 and outlined in Figure 1, it is hypothesized that specific sequences of premature stimulus intervals (including SLSS and similar sequences) can, through the influence of APD and CV restitution, cause enhanced spatial dispersion of repolarization, leading to spatially discordant APD alternans, conduction block, reentry, and VF. This sequence of events provides an explanation for the observation that certain patterns of premature complexes, including short‐long‐short,5 long‐short3 and short‐long,4 promote reentry, VT, and VF. In this study, we confirmed that the coupled maps model, when supplied with APD restitution data from canine right ventricles, predicted the presence of discordant alternans, in the form of beat‐to‐beat patterns of sign changes in spatial gradients of APD and DI, when compared with observations from optical mapping data.…”
Section: Discussionmentioning
confidence: 85%
“…A substantial proportion of sudden cardiac arrests, approximately half in a recent study,2 are associated with ventricular tachycardia (VT) or ventricular fibrillation (VF). It has been observed clinically that sustained VT and VF are often preceded by several irregularly timed premature complexes,3, 4 and studies conducted to explore this phenomenon have shown that specific coupling interval patterns of premature complexes, such as short‐long‐short5 and short‐short‐short,6 tend to lead to reentry and VT. Various researchers have examined the mechanism by which premature complexes or pacing history can interact with electrical restitution properties, including the dependence of action potential duration (APD) and conduction velocity (CV) on the preceding diastolic interval (DI) to produce dynamical heterogeneity of refractoriness, wave break, reentry, and VF7, 8, 9, 10, 11 (see elsewhere12, 13 for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Vulnerability to re-entry is highly influenced by the tissue substrate that a trigger encounters. Heterogeneities naturally exist in the heart 8,9 and are amplified by electrical and structural remodeling in diseased hearts, [10][11][12] by nonuniform cell coupling, [13][14][15] and by inexcitable obstacles. [16][17][18] Heterogeneities can also be induced or modulated by premature extrasystoles or changes in heart rate, 8,9,[19][20][21][22][23][24][25] and thereby affect the VF threshold.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Heterogeneities can also be induced or modulated by premature extrasystoles or changes in heart rate, 8,9,[19][20][21][22][23][24][25] and thereby affect the VF threshold. 26 Early experiments in animal and patients 11,[27][28][29][30][31][32] have demonstrated that both dispersion of refractoriness and inducibility of re-entry are affected by the activation sequence of the premature extrasystoles. In the clinical setting, multiple successive extrasystoles are often involved in the initiation of re-entry.…”
Section: Introductionmentioning
confidence: 99%